Work on the musical phrase, style and artistic image in works of small forms - Moiseeva V. V. (Pedagogical excellence and pedagogical technologies, 2016)
this article presents the experience of working with a pianist pupil. The author describes the methods of the performing skills and mastering the features of polyphony performance (Bach Bure) frormation, as well as disclosure of expressiveness in the performance of image content of a musical work - N. Toropova's romance .
Keywords: фортепиано; открытый урок; романс; полифония; бурре; бах; фраза; миниатюра; гимнастика Стрельниковой; piano; open class; romance; polyphony; Bourree; Bach; phrase; miniature; Strelnikova's gymnastics